Knowledge, attitude and perceptions on second hand smoke (SHS) exposure among undergraduate students contribute to avoidance of second hand smoke - Mohd Zulkefli, Nor Afiah; Ismail, Suriani; Harith Fadzilah, Siti Rohaiza Aida; Abdul Razak, Muhamad Syahir Asyraf (Community Health Society Malaysia, 2017)
Background: Second Hand Smoke (SHS) exposure is a potentially preventable environmental pollutant that has caused rising concern among the public. The avoidance behavior towards Second Hand Smoke exposure is believed to be related to many factors. The objective of this study is to determine the second hand smoke (SHS) avoidance and its associated factors among undergraduate students in a public university in Malaysia. Materials and Methods: A cross-sectional study has been conducted on 395 undergraduate students using validated self-administered questionnaire. Simple random sampling was used in selecting the respondents. The questionnaire was divided into knowledge on SHS exposure, attitude towards avoiding SHS, perception on SHS and SHS avoidance scale. Spearman rank correlation was used to examine the association between knowledge, attitude and perceptions on SHS exposure and avoidance among the respondents. Result: The findings of this study showed the median and interquartile range for knowledge, attitude and perceptions on SHS were 12.0 (3.0), 50.0 (10.0) and 15.0 (3.0) respectively. Whereas the median on avoidance of SHS exposure was 59 (13.0). There were significant correlation between knowledge on SHS exposure (p = 0.010), attitude towards avoiding SHS (p < 0.001) and perception on SHS (p = 0.001) with SHS avoidance score. Conclusion: Knowledge, attitude and perceptions on SHS were significantly correlated with avoidance of SHS. The result of this study will give a useful data for avoidance of SHS intervention programs for undergraduate university students.